Nigericin Promotes NLRP3-Independent Bacterial Killing in Macrophages - Armstrong, Heather; Bording-Jorgensen, Michael; Chan, Richard; Wine, Eytan (Frontiers in Immunology, 2019)
Altered microbiota has been associated with a number of diseases, including inflammatory bowel diseases, diabetes, and cancer. This dysregulation is thought to relate the host inflammatory response to enteric pathogens. Macrophages play a key role in host response to microbes and are involved in bacterial killing and clearance. This process is partially mediated through the potassium efflux-dependent, cytosolic, PYCARD-containing inflammasome protein complex. Surprisingly, we discovered an alternative mechanism for bacterial killing, independent of the NLRP3 inflammasome/PYCARD. Using the NLRP3 inflammasome-deficient Raw 264.7 and PYCARD-deficient J77 macrophages, which both lack PYCARD, we found that the potassium efflux activator nigericin enhances bacterial killing. Macrophage response to nigericin was examined by RT gene profiling and subsequent qPCR, which demonstrated altered expression of a series of genes involved in the IL-18 bacterial killing pathway. Based on our results we propose a model of bacterial killing, unrelated to NLRP3 inflammasome activation in macrophage cells. Improving understanding of the molecular pathways driving bacterial clearance within macrophage cells will aid in the development of novel immune-targeted therapeutics in a number of diseases.